Pengembangan Buku Lesson Study khusus Pendidikan Biologi Berbasis Pendekatan Saintifik - Jodion Siburian; Ali Sadikin; Muhammad Yusuf; Dian Arisandy Eka Putra Sembiring (Jurnal Penelitian Pendidikan IPA, 2023)
Prospective biology teachers need to be well prepared, not only in terms of biology content but also their teaching skills, including lesson study. This study aims to developing a biology lesson study book based on scientific approach. The research method used is research and development by adopting the ADDIE model. The research instrument used was a questionnaire to measure the responses of experts, teachers and students to the quality of the book. This research also pays attention to qualitative (suggestions and comments) and quantitative data. The results showed that the book was considered feasible by experts. Teacher and student responses also showed a positive impact on the use of the book. The test results also showed an increase in learning outcomes. So, the book can be used in classroom learning.